2018
DOI: 10.21608/edj.2017.77062
|View full text |Cite
|
Sign up to set email alerts
|

Dental arch expansion after alveolar cleft repair using autogenous bone marrow derived mesenchymal stem cells versus autogenous chin bone graft

Abstract: Alveolar cleft repair is well established, with bone grafting in mixed dentition phase. Mesenchymal derived stem cells were applied to different kinds of bone substitute and compared in different animal models..This study aimed to evaluate the bone quality and quantity at the alveolar cleft sites that were repaired with autogenous mesenchymal stem cell and its effect on orthodontic dental arch expansion and compare these results with cases treated with autogenous chin bone graft. Patients and methods:16 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Ten controlled (and 18 uncontrolled) studies reported the implantation of autologous MSCs from bone marrow or adipose tissues (Table , Supporting Information Table ). Culture‐expanded BMSCs were used in SA (Hernandez Alfero et al., ; Kaigler et al., , ), RA (Bajestan et al., ) or AC repair (Khalifa & Gomaa, ). Of these, the former four studies reported the use of a commercial automated bioreactor system (Replicell ® or Ixymyelocel‐t ® , Aastrom Biosciences Inc., Ann Arbor, MI, USA) for isolation of a mixed population of CD90 + MSCs, HSCs, endothelial and inflammatory cells, termed “tissue repair cells” (TRCs), from the MNC‐fraction of bone marrow (Bartel et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Ten controlled (and 18 uncontrolled) studies reported the implantation of autologous MSCs from bone marrow or adipose tissues (Table , Supporting Information Table ). Culture‐expanded BMSCs were used in SA (Hernandez Alfero et al., ; Kaigler et al., , ), RA (Bajestan et al., ) or AC repair (Khalifa & Gomaa, ). Of these, the former four studies reported the use of a commercial automated bioreactor system (Replicell ® or Ixymyelocel‐t ® , Aastrom Biosciences Inc., Ann Arbor, MI, USA) for isolation of a mixed population of CD90 + MSCs, HSCs, endothelial and inflammatory cells, termed “tissue repair cells” (TRCs), from the MNC‐fraction of bone marrow (Bartel et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The pre-expansion alveolar cleft has a smaller soft tissue and bone defect, and studies have shown that expansion can be successfully performed after grafting. 16,17 Expansion also provides postgraft stimulation that may encourage maturity and decrease resorption of the bone graft. 18…”
Section: Discussionmentioning
confidence: 99%